(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Working in multinational corporations (MNCs), multicultural work environments present obstacles. In today’s tumultuous workplace, it’s more crucial than ever for businesses to ensure that their employees are happy and productive. This is because increasing production is dependent on employee contentment. The paper attempts to elucidate three critical factors that affect an organization’s corporate culture. The three factors that form the crux of the argument are Psychological Capital, optimism, and workplace happiness. The study was conducted on 101 employees from the service Industry. Both employee psychological capital and optimism are significantly related to greater work happiness within and across time. PsyCap and Optimism are strongly correlated with work place happiness. An employee who has an optimistic mindset can see, understand, and adapt things better as they can understand that the new initiative might bring something positive or modified. Conclusions and implications were discussed for the findings, and limitations were also discussed.